Serum uric acid is no more a by-stander for risk of cardiovascular diseases in metabolic syndrome: a prospective study - Allam, Anirudh Kumar; Chavan, Chandrakant; Mandole, Rahul; Hiremath, Jagdish; Khese, Vikrant (International Journal of Advances in Medicine, 2021)
Background: Cardiovascular diseases have become the fastest growing health issue in India and worldwide. Population with metabolic syndrome is known to be pre-disposed to several chronic disorders along with higher risk of experiencing cardiovascular events. The role of uric acid as a cardiovascular risk factor in metabolic syndrome was not well studied in the literature, which made us to undertake the present study. Methods: All the patients aged between 18 to 75 years (both gender) who approached Madhavbaug cardiac care clinics located in Maharashtra, India for assessing risk of heart disease from January 2015 to January 2017 were screened. Risk factors for metabolic syndrome have been evaluated among the study population and categorised into metabolic syndrome positive (³3 risk factors) and negative groups (<3 risk factors). Statistical analysis was done using SPSS software version: 21.0. Results: Our study includes 2294 subjects who met the inclusion and exclusion criteria. Males outnumbered the females and sex ratio was 2.89:1. Females had lower serum uric acid levels compared to males irrespective of metabolic component. Gender and serum uric acid levels (high and low) were used stratification of the subjects. Serum uric acid is an independent predictor of cardiovascular diseases with an Odds ratio of 1.13 (95% confidence interval). Conclusions: Serum uric acid level is one of the important predictor for cardiovascular risk in metabolic syndrome. Raised uric acid is not an innocent by-stander and one of the major contributors in development of cardiovascular diseases.